KERAGAAN GENERASI KETIGA (M3) KEDELAI HASIL IRADIASI SINAR GAMMA PADA KONDISI OPTIMUM DAN KONDISI CEKAMAN KEKERINGAN - Diana Sofia Hanafiah (Jurnal Pertanian Tropik, 2015)
The objective of this research was to obtain a genotype of selected putative mutant withgood agronomic traits and high yielding on the optimum condition and its adaptability todrought stress in M3 generation. The study result showed that there were differences in thegrowth and production of each population as a result of irradiation in optimum conditions anddrought stress conditions. The population as a result of irradiation at 150 Gy and 200 Gy had a highermean value for the plant height trait, the number of productive branches, the number of productivenodes and the number of productive pods compared to irradiation population of 50 Gy, 100 Gy andthe control population of Argomulyo at optimum conditions. The decrease in the growth anddevelopment happened to all the characters observed in the irradiation population in droughtconditions compared to when grown in optimum conditions. The decrease can be seen in thecharacters of plant height, the number of pods and seed weight per plant. The growth and developmentof the population irradiation of 150 Gy and 200 Gy were more influenced by drought conditionscompared to other irradiation populations. The selection in the optimum conditions produced 291high yielding genotypes and the selection in drought conditions generated 202 genotypes andadapted to drought environments.